INDUSTRIAL AUTOMATION AND ROBOTICS techniques and applications. - Kumar, K. (Kaushik), 1968-; Babu, Sridhar B. ([S.l.] : CRC PRESS, 2022)
This book discusses the radical technological changes occurring due to Industry 4.0, with a focus on offering a better understanding of the Fourth Industrial Revolution. It also presents a detailed analysis of interdisciplinary knowledge, numerical modeling and simulation, and the application of cyber-physical systems, where information technology and physical devices create synergic systems leading to unprecedented efficiency. The book focuses on industrial applications of automation and robotics. It covers recent developments and trends occurring in both computer-aided manufacturing techniques, as well as computer-aided assembly techniques. Robots using embedded systems and artificial intelligence applications are also covered. Industrial Automation and Robotics: Techniques and Applications offers theoretical results, practical solutions, and guidelines that are valuable for both researchers and those working in the area of engineering.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / CAD-CAM; TECHNOLOGY / Robotics; TECHNOLOGY / Manufacturing; Robots, Industrial; Automation